Pemodelan Arsitektur Teknologi pada Perusahaan Palet PT.X menggunakan Enterprise Architecture Planning - Fanny Febriani Santoso; Adi Wibowo; Agustinus Noertjahyana (Jurnal Infra, 2016)
PT. X is a company engaged in the pallet industry, such as the production of wooden pallets, plastic pallets distribution, ISPM#15 services, and the services of container checkers. Until now, not all business processes are being supported by information systems because there are many business processes being done manually and the existing information systems are not yet integrated. Existing information systems in the company only supports finance and accounting process. Based on this condition, this thesis will analyze and construct enterprise architecture design for PT. X using Enterprise Architecture Planning method. The first stage will be done with business modeling and analysis of business strategy company. After that, the next step is to see the condition of the company's information technology at the moment, the existing problems within the company, and information technology needs in the future. Then from these, the results will be constructed by making design data architecture, application architecture, and technology architecture. Data architecture generates multiple subsystems at the company, such as sub-system of sales, sub-system of purchase, sub-system of production, sub-system of ISPM # 15, sub-system of container checker, sub-system of IT, sub-system HRD, and sub-system of finance and accounting. Application architecture consists of several main and supporting applications, all application are web-based. The main application consists of sales information systems, purchase information systems, production information systems, ISPM#15 information systems, container checker information systems, IT information systems, HRD information systems, and financial and accounting information systems. Technology architecture uses a client/server architecture pattern with data services Service Oriented Architecture (SOA).